-1 is the rest, because its degree is smaller than that of the divisor and therefore can not continue dividing.
x ^ 3 - x ^ 2 + x -1 is the quotient.
I attach the solution
Answer:
is used to prove the given equation.
Step-by-step explanation:
We have given an equation:
![sinx\cdot cosx\cdot tanx=1-cos^2x](https://tex.z-dn.net/?f=sinx%5Ccdot%20cosx%5Ccdot%20tanx%3D1-cos%5E2x)
We will consider right hand side first
tan x can be written as:
![tanx=\frac{sinx}{cosx}](https://tex.z-dn.net/?f=tanx%3D%5Cfrac%7Bsinx%7D%7Bcosx%7D)
So, on substituting tan x in the left hand side of the given equation we get:
![sinx\cdot cosx\cdot \frac{sinx}{cosx}](https://tex.z-dn.net/?f=sinx%5Ccdot%20cosx%5Ccdot%20%5Cfrac%7Bsinx%7D%7Bcosx%7D)
Cancel common term from denominator and numerator which is cosx we get
![sin^2x](https://tex.z-dn.net/?f=sin%5E2x)
And we have an identity:
![sin^2x+cos^2x=1](https://tex.z-dn.net/?f=sin%5E2x%2Bcos%5E2x%3D1)
![\Rightarrow sin^2x=1-cos^2x](https://tex.z-dn.net/?f=%5CRightarrow%20sin%5E2x%3D1-cos%5E2x)
Hence, right hand side is equal to
.
Answer:
18 and 9
Step-by-step explanation:
The numbers are x and 1/2x.
x + 1/2x = 27
3/2x = 27
x = 18 so the numbers of 18 and 9.
The function f(g(2)) is an illustration of a composite function
The value of f(g(2)) is 2
<h3>How to determine the value of the function f(g(2))?</h3>
Given:
The table of values for functions f(x) and g(x)
To calculate f(g(2)), we start by calculating g(2)
From the table;
g(2) = 6
So, we have:
f(g(2)) = f(6)
From the table;
f(6) = 2
So, we have:
f(g(2)) = 2
Hence, the value of f(g(2)) is 2
Read more about composite functions at:
brainly.com/question/10687170